2010
DOI: 10.1021/ef901120h
|View full text |Cite
|
Sign up to set email alerts
|

Fast Pyrolysis of Pine Sawdust in a Fluidized-Bed Reactor

Abstract: Pine (Pinus strobus) sawdust was pyrolyzed in a fluidized-bed reactor between the temperatures of 400 and 600 °C. The fixed-bed volume and residence time were optimized to maximize the liquid yield. We report the detailed physical and chemical properties of the bio-oil fraction collected during fast pyrolysis. The liquid yield was maximized at 500 °C, whereas increased gas formation occurred at 600 °C. 13C NMR of the bio-oil fractions indicated a decrease in the carbohydrate fraction and an increase in the aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 33 publications
14
96
2
Order By: Relevance
“…The pulverized bio-char had higher fixed carbon content (88.89% at 700 °C).The fine particle size let the heat transfer much easily, thus making the pyrolysis of pulverized bio-char more complete. In other studies (DeSisto et al 2010;Amutio et al 2012;Ronsse et al 2013), the fixed carbon content showed the same trend with slightly different values. These analyses showed that pyrolysis is an impurity removal process.…”
Section: Proximate Analysismentioning
confidence: 51%
See 2 more Smart Citations
“…The pulverized bio-char had higher fixed carbon content (88.89% at 700 °C).The fine particle size let the heat transfer much easily, thus making the pyrolysis of pulverized bio-char more complete. In other studies (DeSisto et al 2010;Amutio et al 2012;Ronsse et al 2013), the fixed carbon content showed the same trend with slightly different values. These analyses showed that pyrolysis is an impurity removal process.…”
Section: Proximate Analysismentioning
confidence: 51%
“…Other species of bio-char show the same trend (Ronsse et al 2013;Guo and Bi 2015), but different kinds of biomass are quite different in ash content. The ash content of pulverized bio-char was much lower than that in the molded form, which is similar to pulverized sawdust bio-char (DeSisto et al 2010;Amutio et al 2012;Ronsse et al 2013). In briquette process, the volatiles in lignin and hemicelluloses would become slightly reduced.…”
Section: Proximate Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…Other names used for these types of setups are: screen-heater, captive sample reactor, wire net apparatus and heated grid reactor. Different types of feedstock (coal [19][20][21][22][23][24][25][26][27][28][29][30] , plastic 31 , cellulose 14,32,33 , lignin 34,35 , and biomass ) were (hydro) pyrolyzed/combusted. An overview of wire-mesh reactors used to study the fast pyrolysis process of biomass/model compounds is listed in Table 2.1 and will be discussed briefly.…”
Section: Overview Wire-mesh Reactorsmentioning
confidence: 99%
“…HPLC analyses were carried out to qualify the sugars (Agilent 1200 serie, PL Hi-PlexH (300•7.7 mm, part no PL 1170-6830) 65 0 C, RID (55 0 C); 0.6 ml/min 5mM H 2 SO 4 ). 1-H-NMR (chapter 2)6 spectra were interpreted by the classification in functional groups as suggested by Ingram et al 35 .…”
Section: Oilmentioning
confidence: 99%